SAT0509 Dynamics in the levels of adipokines and cytokines in parallel with weight loss and their relationship with clinical manifestations of knee osteoarthritis. (15th June 2017) - Strebkova, E; Solovyova, I; Mkrtumyan, A; Alekseeva, L
Abstract : Background: Untoward effects of pro-inflammatory cytokines on a chondrocyte are implied in pathogenesis of osteoarthritis (OA), while adipokines would enhance these pathogenetic mechanisms and facilitate maintenance of inflammation and progression of OA when the latter is associated with obesity. Objectives: To asses dynamic changes of adipokine (leptin) and pro-inflammatory cytokines (IL-6, TNF-α) levels and their relationship with clinical manifestations of knee OA in pts losing weight during orlistat therapy. Methods: The study included 50 female pts aged 45–65 years with knee OA, Kellgren-Lawrence stage II-III, and obesity (BMI>30kg//m 2 ). Pts form Group 1 (n=25) were receiving orlistat 120 mg x 3 times a day for 6 month combined with low-caloric diet and therapeutic physical exercise. Pts from Group 2 (n=25) were administered only low-caloric diet and therapeutic physical exercise for 6 month. Anthropometry data (height, body weight, BMI), WOMAC and quality of life EQ-5D scores, as well as serum levels of leptin, IL-6 and TNF-α using ELISA were assessed at baseline and at 6 months in all pts. Results: Following pharmacological and non-pharmacological therapy of obesity in pts with knee OA subjects from Group 1 reduced their body weight by 10, 07% ( p <0, 05), and pts from Group 2 - by 0, 84% ( p >0, 05). At baseline pts from both groups did not differ ( p >0, 05) by leptin, IL-6 and TNF-α levels. Decreased leptin levels were documented in pts from Group 1 after 6 months of orlistat therapy ( p =0, 05), which directly correlated with body weight loss (r=0, 5, p =0, 02), total WOMAC score reduction r=0, 5, p =0, 01), and score reduction in WOMAC subscales measuring pain r=0, 5, p =0, 01; stiffness r=0, 4, p =0, 04; and functional insufficiency r=0, 4, p =0, 03, thus reflecting improvement of OA symptoms; and inversely correlated with increased EQ-5D score (r=-0, 4, p =0, 03) reflecting improvement in quality of life. Besides, orlistat therapy was associated with decreased IL-6 levels ( p <0, 05). Both groups demonstrated high TNF-α levels, although some insignificant decrease was noticed in Group 1 ( p =0, 14) following weight loss with orlistat therapy. Persisting leptin, IL-6 and TNF-α levels were registered in pts from Group 2, who maintained their body weight following only life-modifying therapy of obesity. Clear correlations between IL-6 and TNF-α levels and changes in body weight and clinical manifestations of OA were not found in both groups. Conclusions: Significant decrease in leptin and IL-6 levels were observed in knee OA pts following orlistat therapy and associated weight loss. There was a direct correlation between decreased leptin levels and body weight loss, as well as reduction in WOMAC scores reflecting improvement of knee OA clinical manifestations, and inverse correlation with EQ-5D score resulting in quality of life improvement. Therefore, body weight loss following pharmacotherapy of obesity is associated not only with improvement of OA clinical symptoms, but also with down-regulation in production of pro-inflammatory leptin and IL-6, most probably resulting in reduction of meta-inflammation in obese pts with OA. Disclosure of Interest: None declared